Diagnostic reference range of κ/λ free light chain ratio to screen for Bence Jones proteinuria is not significantly influenced by GFR. (26th July 2015) - Schmidt‐Hieltjes, Yvonne; Elshof, Clemens; Roovers, Lian; Ruinemans‐Koerts, Janneke
Abstract: Objectives: The aim of our study was to analyse whether the κ/λ free light chain ratio reference range for screening for Bence Jones proteinuria should be dependent on the estimated glomerular filtration rate (eGFR). Methods: The serum κ/λ free light chain ratio, eGFR, serum M‐protein and Bence Jones protein were measured in 544 patients for whom Bence Jones protein analysis was ordered. Results: In the population of patients without Bence Jones proteinuria or a M‐protein ( n  = 402), there is no gradual increase in κ/λ free light chain ratio with diminishing eGFR. The κ/λ free light chain ratio in this group was 0.56–1.86 (95% interval). With this diagnostic reference range of the κ/λ ratio, 105 of the 110 patients with Bence Jones protein could be identified correctly. Only five patients with Bence Jones proteinuria (<0.17 g/L) were missed, without diagnostic or therapeutic consequences. In 36 patients (6.6%), an abnormal κ/λ free light chain ratio was measured without the presence of Bence Jones proteinuria. Conclusions: A κ/λ free light chain ratio in serum can be used safely and efficiently to select urine samples which should be analysed for Bence Jones proteinuria with an electrophoresis/immunofixation technique. Using this diagnostic reference range, the number of urine samples which should be analysed by electrophoresis/immunofixation could be reduced by 74%. The diagnostic reference interval can be determined best in a group of patients for whom Bence Jones analysis is indicated. For calculation of this reference range, the eGFR value does not need to be taken into account.